2018
DOI: 10.1111/acem.13556
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial of Intravenous Acetaminophen as an Analgesic Adjunct for Older Adults With Acute Severe Pain

Abstract: In this randomized clinical trial, the addition of IV acetaminophen to IV hydromorphone as an adjunctive analgesic for acute, severe, pain in older adults provided neither clinically nor statistically superior pain relief when compared to hydromorphone alone within the first hour of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The only study we could find of the adjunctive use of IV acetaminophen in the ED is one conducted by our research group. 4 That study was restricted to patients aged 65 and older. The methodology was similar to that of the current study, with the exception that the elderly patients enrolled in this earlier trial received 0.5 mg of hydromorphone rather than 1 mg given in the current study of patients under 65 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The only study we could find of the adjunctive use of IV acetaminophen in the ED is one conducted by our research group. 4 That study was restricted to patients aged 65 and older. The methodology was similar to that of the current study, with the exception that the elderly patients enrolled in this earlier trial received 0.5 mg of hydromorphone rather than 1 mg given in the current study of patients under 65 years.…”
Section: Discussionmentioning
confidence: 99%
“…Details of the masking of the medications have been previously described. 4 All patients received a single dose of 1 mg of IV hydromorphone. The nurse retrieved the next sequentially ordered packet from the automated medication dispensing system and then administered the study medication, acetaminophen or placebo, to the patient.…”
Section: Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, it remains unclear why acetaminophen seems to have an opioid‐sparing effect in postoperative use but not in patients presenting to the ED with moderate to severe acute pain. However, given the data on fixed‐dose opioids 13,22,23 or titrated and individualized morphine in this study (not providing evidence of differences in efficacy or side effects), it seems unlikely that acetaminophen would have an effect in ED patients. Furthermore, in ED patients with moderate to severe acute pain, initial analgesia with acetaminophen alone may delay administration of opioids and consecutive pain relief and should therefore not be considered standard treatment.…”
Section: Discussionmentioning
confidence: 81%
“…Alternative and adjunctive therapies to opioids have been recently investigated; however, the study results have been mixed. Most of the studies illustrating significant pain control with IV acetaminophen have been done in populations with acute pain due to fractures, renal colic, or postoperative pain 14,16–18,22–26 . A recent study by Blok et al 20 comparing IV acetaminophen to morphine in adults with acute pain in the ED failed to demonstrate an opioid‐sparing effect but showed that a small number of patients used less opioids in the following 24 hours after discharge.…”
Section: Discussionmentioning
confidence: 99%